Penerapan Model Pembelajaran Cooperative Type Jigsaw Terhadap Peningkatan Keaktifan Belajar Aqidah Akhlak pada Siswa Kelas VIII MTs Al-Fauzul Kabir Kota Jantho - Mashuri, Juairiah Umar, Masthura Muliani. (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2016)
Teachers occupy important positions and determine the success of the learning process. One of the tasks of teachers, is to use a method / model appropriate learning, so that students become active. The reality is based on preliminary observations in MTs Al-Fauzul Kabir, only a limited number are active. Based on these problems researchers tried to use the type cooperative learning model jigsaw particularly on learning Aqidah Morals eighth graders Fauzul MTs Al-Kabir, which aims to enable all students in the learning process. This study uses the approach of PTK, which lasted for two cycles. The results showed that using a model of the type cooperative learning jigsaw on Aqidah Morals can improve students' learning activeness, it can be seen in the first cycle and the second cycle increased. Activities teachers in the first cycle obtain an average value of 2, 75 with a percentage of 68, 7%, in the second cycle obtain an average value of 3.6 with a percentage of 89.6%. While on student activities, cycle 1 scored an average of 2, 7 with a percentage of 66, 6%, while in the second cycle with an average of 3.5 with a percentage of 87.5. Thus it can be said, that uses cooperative learning model type of Jigsaw can enhance the activity of students in the learning process.